2019
DOI: 10.1002/lary.27877
|View full text |Cite
|
Sign up to set email alerts
|

Temporal bone carcinoma: Treatment patterns and survival

Abstract: Objectives/Hypothesis: Carcinomas of the temporal bone are rare, and appropriate treatment, staging, and survival data are limited. This study evaluates clinical characteristics and survival rates for patients with temporal bone carcinoma treated with resection at a single tertiary-care institution, with a focus on the outcomes of patients with locally advanced disease including skull base and/or dural invasion.Study Design: Retrospective chart review. Methods: Demographic, tumor-specific, and survival data we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 27 publications
(41 reference statements)
0
48
0
Order By: Relevance
“…Dural involvement from preoperative imaging studies did not affect long-term tumor control and survival (25). Seligman et al (29) argued that dural invasion need not automatically be considered a surgical contraindication in all cases, noting that three of their four cases of TB-SCC survived for over 5 years following STBR. In our study, the invasion of the posterior cranial fossa dura significantly worsened the DSS rate (27.27%), and invasion of the middle cranial fossa dura showed a high HR (HR = 2.846).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dural involvement from preoperative imaging studies did not affect long-term tumor control and survival (25). Seligman et al (29) argued that dural invasion need not automatically be considered a surgical contraindication in all cases, noting that three of their four cases of TB-SCC survived for over 5 years following STBR. In our study, the invasion of the posterior cranial fossa dura significantly worsened the DSS rate (27.27%), and invasion of the middle cranial fossa dura showed a high HR (HR = 2.846).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors continue to discuss the impact of dural invasion on prognosis ( 7 , 16 , 25 , 27 29 ). In 1994, Parasad et al reported that in cases where dural invasion was present, surgical resection did not improve overall survival after comparing 11 dural invasion cases with resection and nine dural invasion cases without resection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patient T989 had synchronously occurring bilateral EACSCC of both ears ( Figure 3A Although both primary tumors (T939L and T939R) had pathogenic somatic mutations in TP53, their genomic positions were different ( Figure 3C and Table S2). These results suggest that these tumors Fraction of Mutations (%) T 9 3 9 L T 9 3 9 R T 5 0 1 T 7 0 4 T 2 1 0 T 4 6 5 T 3 2 8 T 9 8 1 T 0 9 7 T 3 3 34,35 despite the functional contribution in the onset of EACSCC being unknown (Table S3).…”
Section: Intrapatient Heterogeneity Of Synchronous Bilateral Externmentioning
confidence: 98%
“…External auditory canal squamous cell carcinoma (EACSCC) is a rare and aggressive malignant disease originating from squamous epithelial cells of the external auditory canal, which reportedly occurs in 1 to 6 cases out of 1 000 000 individuals per year, with poor overall survival. [1][2][3][4][5] Because of its rarity, an evidence-based treatment strategy for EACSCC has not yet been established; thus, it is clinically and biologically important to elucidate the molecular characteristics of EACSCC to discover novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%